2023
DOI: 10.1021/acsomega.2c07468
|View full text |Cite
|
Sign up to set email alerts
|

Partial Destabilization of Amyloid-β Protofibril by Methionine Photo-Oxidation: A Molecular Dynamic Simulation Study

Abstract: Selective photosensitized oxidation of amyloid protein aggregates is being investigated as a possible therapeutic strategy for treating Alzheimer’s disease (AD). Photo-oxidation has been shown to degrade amyloid-β (Aβ) aggregates and ameliorate aggregate toxicity in vitro and reduce aggregate levels in the brains of AD animal models. To shed light on the mechanism by which photo-oxidation induces fibril destabilization, we carried out an all-atom molecular dynamics (MD) simulation to examine the effect of meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24] Experiments with Aβ 1-42 peptide under the conditions photosensitized generation of singlet oxygen showed that the Met 35 is a major target for oxidation. [25,26] Interestingly, the oxidation of that particular side chain was previously shown to be an important conformational switch which stops the formation of the toxic oligomers and thus, reduces the overall toxicity Aβ. [27,28] While photogenerated singlet oxygen does serve as an important mechanistic tool, it does not have practical (clinical) potential, considering the highly impeded tissue penetration of light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24] Experiments with Aβ 1-42 peptide under the conditions photosensitized generation of singlet oxygen showed that the Met 35 is a major target for oxidation. [25,26] Interestingly, the oxidation of that particular side chain was previously shown to be an important conformational switch which stops the formation of the toxic oligomers and thus, reduces the overall toxicity Aβ. [27,28] While photogenerated singlet oxygen does serve as an important mechanistic tool, it does not have practical (clinical) potential, considering the highly impeded tissue penetration of light.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the photodynamic generation of singlet oxygen ( 1 O 2 ), was shown to degrade Aβ aggregates in vitro, and resulted in the remission of symptoms in disease models developed in C. elegans , Drosophila and mouse [16–24] . Experiments with Aβ 1–42 peptide under the conditions photosensitized generation of singlet oxygen showed that the Met 35 is a major target for oxidation [25,26] . Interestingly, the oxidation of that particular side chain was previously shown to be an important conformational switch which stops the formation of the toxic oligomers and thus, reduces the overall toxicity Aβ [27,28] .…”
Section: Introductionmentioning
confidence: 99%